NSAIDs increase survival in the Sandhoff disease mouse: synergy with N-butyldeoxynojirimycin. - Jeyakumar, M; Smith, D; Williams, I; Borja, M; Neville, D; Butters, T; Dwek, R; Platt, F (2004)
The GM2 gangliosidoses are caused by incomplete catabolism of GM2 ganglioside in the lysosome, leading to progressive storage and a neurodegenerative clinical course. An inflammatory response (microglial activation, macrophage infiltration, oxidative damage) has been found to be a consequence of GM2 storage in the brain, although it remains unclear whether this contributes to pathogenesis or disease progression. In this study, we treated Sandhoff disease mice with nonsteroidal antiinflammatory drugs (indomethacin, aspirin, and ibuprofen) and antioxidants (L-ascorbic acid and alpha-tocopherol acetate). The treated mice lived significantly longer than untreated littermates (12-23%, p <0.0001) and showed a slower rate of disease progression (p <0.001). When aspirin treatment was combined with substrate reduction therapy, synergy resulted (11%, p <0.05) with a maximum improvement of 73% in survival (p <0.00001). This study demonstrates that inflammation contributes to disease progression and identifies antiinflammatory and antioxidant therapies as a potential adjunctive approach to slow the clinical course of this and related disorders.